2015
DOI: 10.1590/1517-869220152101144430
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de uma sessão de treinamento de força sobre a qualidade do sono de adolescentes

Abstract: INTRODUÇÃO: o sono é uma função biológica fundamental para a conservação da energia e a restauração do metabolismo energético.OBJETIVO: analisar o efeito de uma sessão do treinamento de força realizada em diferentes horários sobre a qualidade do sono de adolescentes e examinar se a relação entre a melhoria da qualidade do sono e o horário da sessão de treino se altera após o ajuste para idade.MÉTODOS: participaram do estudo seis estudantes do sexo masculino moradores internos do IFPE - Campus Vitória de Santo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
1
Order By: Relevance
“…In another study, Noland et al 23 reported the practice of pre-bedtime physical exercise being cited as one of the strategies used by adolescents to fall asleep. On the other hand, according to Santiago et al, 7 performing a strength training session in the morning or the afternoon improved the sleep quality of adolescents in a boarding school.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In another study, Noland et al 23 reported the practice of pre-bedtime physical exercise being cited as one of the strategies used by adolescents to fall asleep. On the other hand, according to Santiago et al, 7 performing a strength training session in the morning or the afternoon improved the sleep quality of adolescents in a boarding school.…”
Section: Discussionmentioning
confidence: 94%
“… 3 , 4 , 6 When it comes to behavioral factors specifically, practicing exercises has been pointed out as a factor associated with better sleep quality in adolescents. 7 Brand et al 8 studied a sample of adolescents and reported that regular practice of exercises is related to better sleep quality in 38 subjects aged 18 years. Another study showed a single exercise session accounting for approximately 50% of improved sleep quality in adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthening physical exercise is beneficial for reducing the occurrence of anxiety symptoms, and adolescents who exercise more frequently are more likely to have longer sleep hours compared with their peers who exercise less frequently [ 3 , 32 ]. In the past decade, short-term intervention studies find a significant correlation between objectively measured sleep hours and physical exercise [ 3 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um fator que pode afetar a qualidade do sono é prática regular de exercício físico. Embora o exercício físico seja aceito pela American Sleep Disorders Association (ASDA) como uma intervenção não-farmacológica para a melhoria do sono 11 , alguns estudos vem demonstrando o efeito benéfico do exercício físico sobre a qualidade do sono 12,13 . Um estudo realizado na cidade de São de Paulo fez um levantamento e demonstrou que entre 27,1 e 28,9% das pessoas fisicamente ativas e 72,9 e 71,1% dos sedentários, se queixavam de insônia e sonolência diurna excessiva, respectivamente 14 .…”
Section: Introductionunclassified